Reforming Legal Frameworks for Human Capital: Digital Strategies Driving Industry 5.0 and Sustainability - Tjokro, Gunawan; Zaenuri, Zaenuri; Yanto , Heri; Rokhman, Fathur; Rajagukguk, Abdul; Sanni, Tajudeen (Journal of Law and Legal Reform, 2025)
The transition to Industry 5.0 necessitates a robust legal framework to regulate human capital investment, ensuring digital workforce development aligns with labor protections and Sustainable Development Goals (SDGs). This study examines the regulatory structures governing human capital investment in Indonesia, the European Union, and the United States, evaluating their effectiveness in addressing digital transformation challenges, AI-driven employment governance, and workforce adaptability. A mixed-methods approach integrates legal analysis with empirical assessments of policy effectiveness, workforce investment trends, and labor market outcomes. Findings reveal significant disparities in AI workforce governance, skill accreditation, and automation labor rights. Indonesia’s fragmented legal framework hinders workforce reskilling and AI employment governance, while the European Union’s AI Act provides a structured, albeit inconsistently implemented, model for digital employment regulation. The United States, despite its technological leadership, lacks federal AI workforce policies, leading to state-level regulatory variations. The study underscores the necessity of harmonized legal frameworks to bridge workforce skill gaps, protect labor rights, and advance SDG-aligned workforce policies. Future legal reforms must prioritize AI governance, digital workforce training, and cross-border labor protections to ensure equitable workforce transitions. Strengthening public-private partnerships, standardizing AI employment regulations, and enhancing labor rights enforcement will be essential for fostering sustainable human capital investment in the industry 5.0 era. The contribution of research extends beyond theoretical frameworks, providing substantial implications for policy formulation, industry practices, educational advancements, and societal improvements.